Participação popular ou participação tutelada? Análise do desenvolvimento da Agenda 21 local em Barueri - Bento, Fabiana da Silva (2012)
This thesis discusses the popular engagement issue in public policies and it is supported by the analysis of the local Agenda 21 in Barueri. It is based on the theoretical review about this participation, since the existence of the subject among social movements in Europe until it has been discussed in Brazil. From this review it is possible to broach theoretical aspects of the political bargaining with a view to offset the existing and legitimated political practices towards the dilemma originated from the implementation of participatory actions. The study has been conducted under the perspective of field-subject and it has been supported by readings. It has been observed the difficulty in promoting changes into the way policies have been addressed in Barueri, which demonstrates the government’s inability to mobilize the population and emphasizes how important and reliable participative practices are. This work intends to point out the failures and dilemmas found in this process and it suggests ways to evaluate and discuss the implementation of popular participation as a new political practice.